2021
DOI: 10.1038/s41746-021-00463-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictive analytics and tailored interventions improve clinical outcomes in older adults: a randomized controlled trial

Abstract: This study explored the potential to improve clinical outcomes in patients at risk of moving to the top segment of the cost acuity pyramid. This randomized controlled trial evaluated the impact of a Stepped-Care approach (predictive analytics + tailored nurse-driven interventions) on healthcare utilization among 370 older adult patients enrolled in a homecare management program and using a Personal Emergency Response System. The Control group (CG) received care as usual, while the Intervention group (IG) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A digital health tool that is useful in practice is one that is able to trigger a specific workflow: the insight that the tool provides must be translated into an actual human intervention in order to realize the tool’s value 25 . Prior work suggests that predictive models have the capacity to move the needle on clinical outcomes when their output is coupled with tailored human interventions 26 . Thus, both the tool’s target-outcome metric and its ability to affect this outcome metric must be considered.…”
Section: Is There a Clear Demonstration Of Clinical Value?mentioning
confidence: 99%
“…A digital health tool that is useful in practice is one that is able to trigger a specific workflow: the insight that the tool provides must be translated into an actual human intervention in order to realize the tool’s value 25 . Prior work suggests that predictive models have the capacity to move the needle on clinical outcomes when their output is coupled with tailored human interventions 26 . Thus, both the tool’s target-outcome metric and its ability to affect this outcome metric must be considered.…”
Section: Is There a Clear Demonstration Of Clinical Value?mentioning
confidence: 99%
“…Studies have demonstrated the use of computational modeling in medicine, which involves creating novel diagnostic tests and determining appropriate treatment plans for patients with specific diseases [7]. An example of such research involved building a computational model that accurately predicted mortality rates among acute myeloid leukemia patients [8].…”
Section: Selected Clinical Applicationsmentioning
confidence: 99%
“…Regular updates and refinement of predictive models based on new data are necessary to maintain accuracy. Healthcare providers should be trained to interpret and act on predictive insights to improve patient care [40].…”
Section: Data Collection and Analysismentioning
confidence: 99%